Merit aid and sorting: the effects of HOPE-style scholarships on college ability stratification - Christopher Mark Cornwell; David B. Mustard (Institute for the Study of Labor (IZA), 2006)
In the last fifteen years there has been a significant increase in merit aid. Coincident with this increase in merit aid has been increased attention to sorting in various aspects of life, especially in education. This paper examines the extent to which merit-based aid exacerbates or ameliorates sorting by ability in higher education. We use panel data from Peterson's Guide to Colleges and the Integrated Postsecondary Education Data System (IPEDS) to evaluate this relationship. Our difference-in-differences estimates show that HOPE increased the quality of entering freshmen in Georgia institutions relative to their out-of-state peers. At the highest-quality institutions HOPE raised all measures of student quality and the homogeneity of students by ability. The lowest-quality institutions experienced no statistically significant effect from HOPE on any measure of student quality. We conclude that state-sponsored merit aid programs increased the retention of high ability students for college and also increased the ability stratification of institutions within states. We also examined two indirect measures of student selectivity-acceptance and yield rates. HOPE decreases acceptance rates at all types of institutions, but the percentage change is largest at the universities, which are most space constrained. HOPE increased yield rates for universities but not for any other institution categories. Together these results suggest that HOPE substantially increased the selectivity at universities.
Keywords: I2; 330; education; sorting; stratification